Brivaracetam exhibits mild pro-inflammatory features in an in vitro astrocyte-microglia co-culture model of inflammation - Ismail, Fatme Seval; Faustmann, Pedro M.; Kümmel, Marie-Luise; Förster, Eckart; Faustmann, Timo Jendrik; Corvace, Franco (Frontiers in Cellular Neuroscience, 2022)
Implications of glia in the pathophysiology of epilepsy raise the question of how these cells besides neurons are responsive to antiseizure medications (ASMs). Understanding ASM effects on glia and glia-mediated inflammation may help to explore astrocytes and microglia as potential targets for alternative anti-epileptogenic therapies. The aim of this study was to investigate the effects of the new generation ASM brivaracetam (BRV) in an astrocyte-microglia co-culture model of inflammation. Primary rat astrocytes co-cultures containing 5%–10% (M5, “physiological” conditions) or 30%–40% (M30, “pathological inflammatory” conditions) of microglia were treated with different concentrations of BRV (0.5, 2, 10, and 20 μg/ml) for 24 h. Glial cell viability was measured by MTT assay. Microglial activation states were analyzed by immunocytochemistry and astroglial connexin 43 (Cx43) expression by Western blot analysis and immunocytochemistry. Gap-junctional coupling was studied via Scrape Loading. Incubation with high, overdose concentration (20 μg/ml) of BRV significantly reduced the glial cell viability under physiological conditions (p < 0.01: **). Treatment with BRV in therapeutic concentrations (0.5 and 2 μg/ml) reduced the resting microglia (p < 0.05: *) and increased the microglial activation under inflammatory conditions (p < 0.01: **). Astroglial Cx43 expression was not affected. The gap-junctional coupling significantly increased only by 0.5 μg/ml BRV under physiological conditions (p < 0.05: *). Our findings suggest mild pro-inflammatory, in vitro features of BRV with regard to microglia morphology. BRV showed no effects on Cx43 expression and only limited effects on gap-junctional coupling. Reduction of glial viability by overdose BRV indicates possible toxic effects.